The Correlation Between Serum Adiponectin Levels and Proinflammatory Cytokines’ Levels, APACHE-II Scores and Mortality in Patients with Intra-Abdominal Sepsis - Dikmen, Kürşat; Yılmaz, Tonguç Utku; Kerem, Mustafa; Bostancı, Hasan; Dikmen Uğraş, Asiye; Paşaoğlu, Özge; Taşçılar, Öge; Karakan, Tarkan (Acıbadem Mehmet Ali Aydınlar Üniversitesi, 2019)
ABSTRACT Objectives: Adiponectin is an anti-inflammatory cytokine that is abundantly produced by adipocytes and have a wide range of effects in sepsis pathophysiology. This study was conducted to investigate whether there is a correlation between serum adiponectin, proinflammatory cytokines’ levels, APACHE-II scores and mortality rates of the patients with sepsis, severe sepsis and septic shock. Patients and Methods: Forty-five patients who met the criteria for sepsis (n=18), severe sepsis (n=14) and septic shock (n=13) were included in this prospective study. Patients who underwent elective abdominal surgery without sepsis were identified as the control group. After the diagnosis of sepsis, blood samples were taken on the following 5 days for adiponectin, IL-6, IL-1β, TNF-α and procalcitonin levels. APACHE-II scores of the patients were calculated daily. All patients were followed for 28 days and mortalities were observed. Results: Ten of the patients died within 28 days. The serum adiponectin levels of the patients in the study group were statistically higher than those in the control group. Statistically, the adiponectin levels of the patients in the septic shock group were markedly lower than those of the patients in sepsis and severe sepsis groups. Serum adiponectin levels inversely correlated with blood levels of IL-6, IL-1β, TNF-α, procalcitonin, lactate and APACHE-II scores. Serum adiponectin levels were significantly higher in survivors. Conclusion: Adiponectin levels reveal differences between sepsis, severe sepsis and septic shock groups. In patients with septic shock, serum adiponectin levels were associated with mortality among patients. Serum adiponectin levels might be a negative predictive marker in patients with sepsis, severe sepsis and septic shock.